2022
DOI: 10.1249/mss.0000000000002938
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Expiratory Flow Limitation during Exercise in Healthy Males and Females

Abstract: RationaleIt is unclear whether the frequency and mechanisms of expiratory flow limitation (EFL) during exercise differ between males and females.PurposeThis study aimed to determine which factors predispose individuals to EFL during exercise and whether these factors differ based on sex. We hypothesized that i) EFL frequency would be similar in males and females and ii) in females, EFL would be associated with indices of low ventilatory capacity, whereas in males, EFL would be associated with indices of high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In the present study, ventilatory drive was evaluated through HVR at rest and during low-intensity exercise. A high variability in individual ventilatory responses has been observed in the present (30) 77.8% 37.5% Chi 2 (1) = 8.510, P = 0.004 Normoxia EFL (28) 70.4% 37.5% Normoxia non-EFL (23) 29.6% 62.5% Chi 2 (1) = 5.545, P = 0.019 study (Table 3). Such variability is commonly reported (44).…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, ventilatory drive was evaluated through HVR at rest and during low-intensity exercise. A high variability in individual ventilatory responses has been observed in the present (30) 77.8% 37.5% Chi 2 (1) = 8.510, P = 0.004 Normoxia EFL (28) 70.4% 37.5% Normoxia non-EFL (23) 29.6% 62.5% Chi 2 (1) = 5.545, P = 0.019 study (Table 3). Such variability is commonly reported (44).…”
Section: Discussionsupporting
confidence: 52%
“…In within-group comparisons of this study, the CrossFit athlete group showed a high positive correlation, and the sedentary group without comorbidities showed a moderate positive correlation when FVC and FEV1 were analyzed; that is, despite these variables not being affected by the strength of the respiratory muscles, if the FVC increased, FEV1 was likely to increase. This observation is important because FEV1 is generally considered an effort-dependent pulmonary parameter, and higher values depend on the abdominal muscles, which are mainly active during expiration (Molgat-Seon et al, 2022). Although not similar, studies on the effect of exercise on lung function have been performed who observed improvement in FVC and FEV1 in participants with overweight and obese after 24 weeks of exposure to aerobic exercise (Azad et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…EFL, when present, was associated with lower peak trueV̇normalE${\dot{V}}_{\rm{E}}$ in females. Lower mid‐expiratory flows and lower expiratory reserve volume as a fraction of FVC (indicators of ventilatory capacity) and higher V T (%FVC) and f B (indicators of ventilatory demand) can help predict whether EFL occurs during exercise (Molgat‐Seon et al., 2022). However, a larger sample would be needed to explore sex differences in how ventilatory capacity and demand interact to produce EFL among males and females with obesity.…”
Section: Discussionmentioning
confidence: 99%